The Relationship Between Prior Knowledge and EFL Learners' Listening Comprehension: Cultural Knowledge in Focus - Samian, Samira Hayati; Dastjerdi, Hossein Vahid (Richtmann Publishing, 2012)
The present study investigated the impact of cultural familiarity on improving Iranian EFL learners’ listeningcomprehension. To do this, forty English language learners were selected at a private language institute in Isfahan based ontheir scores in FCE test and were randomly assigned to four groups of ten. A pre-test was administered to the four groups beforeany treatment. During the experiment, Group A had exposure to target culture texts. The participants in Group B had exposure tointernational target culture texts. The participants in Group C had exposure to source culture texts. The participants in Group Dhad only exposure to culture free texts. At the end of this treatment, the four groups took a post-test which was the same as pretestto see whether the treatment had any influence on their listening proficiency. The results of the post-test showed that thefour groups performed differently on the post-test, which indicated that greater familiarity with specific culturally-orientedlanguage listening material would improve Iranian EFL learners’ listening proficiency.